2022
DOI: 10.1039/d2py00851c
|View full text |Cite
|
Sign up to set email alerts
|

Poly(sulfur ylides): a new class of zwitterionic polymers with distinct thermal and solution behaviour

Abstract: Zwitterionic polymers have emerged as an important class of hydrophilic polymers and found widespread applications not only in biomedical science but also in nanotechnology as antifouling coatings, drug delivery vesicles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Here, we demonstrate that sulfur ylides, a recently reported new class of zwitterionic polymers, [27] display strong antifouling properties. Our results indicate that the antifouling behaviour is caused by a synergistic effect from induced hydration layers and inhibition of bacterial growth.…”
Section: Introductionmentioning
confidence: 66%
“…Here, we demonstrate that sulfur ylides, a recently reported new class of zwitterionic polymers, [27] display strong antifouling properties. Our results indicate that the antifouling behaviour is caused by a synergistic effect from induced hydration layers and inhibition of bacterial growth.…”
Section: Introductionmentioning
confidence: 66%
“…Yet, the restricted structural diversity and chemical space of N -oxides hamper further advancements. Our group explored the use of sulfur ylides as the zwitterionic residue for antifouling materials, where the negative charge is localized on a carbon and the positive charge on a sulfonium residue. , Our results indicated that coatings from poly­(sulfur ylides) not only induce a strong hydration layer but also provide a hostile environment selectively to bacteria. Consequently, we observed that those bacteria that overcome the physical barrier of hydration experience a bactericidal environment.…”
mentioning
confidence: 99%
“…Recently, our group and the group of S. Jiang have independently reported poly­(ylides) as a new class of unexplored zwitterionic materials (Figure ). This long-overlooked class of polymers features some distinct structural properties, namely, a positive charge directly adjacent to a negative charge, thereby being in strong contrast to polybetaines that typically have a carbon spacer between the charges. The Jiang group disclosed N -oxides and demonstrated their ultralow antifouling properties in mice models …”
mentioning
confidence: 99%